PELATIHAN DAN PENDAMPINGAN PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING BERBANTUAN BAHAN AJAR ELEKTRONIK BAGI GURU KELAS IV SDIT INSAN MULIA KOTA BENGKULU - Agusdianita, Neza; Ken Kustianti, Sri; Resnani, Resnani (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The school that is being used as a partner for the PKM IPTEKS activity that is being proposed is SDIT Insan Mulia, Bengkulu City. The school continues to run face-to-face and online learning during the COVID-19 pandemic. The school reduced the number of students in one class and reduced the hours of lessons each day. Based on interviews with teachers at SDIT Insan Mulia, information was obtained that the impact of these rules was that the learning process could not run effectively. Teachers are limited in determining the appropriate method during face-to-face learning at school and teachers are also not skilled at utilizing electronic teaching materials as long as students study independently from home. Blended learning is one of the learning solutions that can be applied during a pandemic. The most common meaning of blended learning is the combination of face to face learning (face to face) with online-based learning. Teachers can run face-to-face learning while at school and continue with online learning if students are at home. As long as students study online at home, teachers can use electronic teaching materials such as videos, pictures, broadcast materials, game applications or google forms to facilitate students to learn independently. The formulation of the problem that is a priority to be resolved through this PKM activity is to train and assist class IV teachers of SDIT Insan Mulia in applying the blended learning model with the help of electronic teaching materials. Thus, teachers are expected to be able to design, implement and evaluate learning that is effective, meaningful, active, innovative, creative and fun. The target audience for this PKM activity are fourth grade teachers and fourth students at SDIT Insan Mulia. The method used in this PKM activity is training and mentoring. The evaluation instruments for this activity are interview sheets, observation sheets and test sheets This activity has been carried out up to training and mentoring for teachers in making and implementing learning tools for class IV SDIT Insan Mulia